News as a Rhetorical Act - Sobczak, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This article presents television news as a rhetorical act. Television news is understood as an account of an event usually comprising of a short introduction and a few minutes of film footage (sometimes referred to as the editorial), created as a result of the work of reporters, broadcast on television, usually as one of the elements in the structure of a news magazine, but also as an element of the programme blocks of news television channels. Television news functions in the media as one of the elements of the strategic actions of media broadcasters, focused on specific purposes, including image-building and political and economic goals. News is created as a response to specific events, it fulfils the need for information, but also serves the creation of a certain image of the world, focusing attention on certain aspects of reality, evaluating it, persuading viewers of the importance or unimportance of certain events. It plays an informative, creative, conceptual, stimulating, evaluative and ultimately aesthetic role. In order to achieve these objectives it is appropriately constructed, taking into account the characteristics and needs of the recipient and the ethos of the broadcaster. In this sense, it is therefore a “rhetorical” act – intentional, deliberate, constituting a response to a specific situation (it is historically, socially and politically conditioned) and addressed to specific recipients.